Modelling the behavior of a reverse-flow catalytic autothermal fixed-bed reactor for production of synthesis gas using methane partial oxidation - Van, Dang Son (Animo Repository, 2005)
The catalytic autothermal fixed-bed reactor with periodic flow reversal is a promising technology for producing synthesis gas using a weakly exothermic process of methane partial oxidation from natural gas. A transient, one-dimensional pseudo-homogeneous model was developed and applied to study a reverse-flow catalytic autothermal fixed-bed reactor for producing syngas using partial oxidation of methane. A numerical method and computer program in MATLAB environment was used to solve the system of model equations. In the mathematical model, the reactor is divided into three sections with different purposes. The left and right inert section is for storing thermal energy from the product stream to supply to the feed stream, whereas the catalyst section is where the chemical reaction takes place. The honeycomb cordierite monolith was used in both inert and catalyst beds. The catalyst was assumed to be NiO/MgO/Al2O3 which is coated on honeycomb cordierite monolith. The behavior of the reactor was analyzed by varying the inlet conditions, initial conditions and the switching period. Maps of the critical parametrically sensitive regions are presented and the influences of various reactor operating parameters were investigated. “True” autothermal operation was achieved because (i) the inlet (feed stream) and outlet (product stream) temperature was close to ambient (300-400K) (ii) no heat from the outside was supplied and 90-99% methane conversion was obtained. The highest yield of hydrogen of about 42% was obtained; the highest yield of carbon monoxide of about 40% was achieved. The set of parameters used for those highest results are maximum initial temperature of 700K, initial partial pressure of methane of 0.7 bar, catalyst portion of 36% of reactor length, oxygen and methane molar ratio of 0.5, hydrogen-methane molar ratio of 0.1, switching time of 100s and velocity of 0.15 m/s. Several sets of useful parameters were suggested for the design and ii operation of a reactor for the partial oxidation of methane in a reverse flow catalytic autothermal fixed-bed reactor. The study improved the further understanding of the behavior of a reverseflow catalytic autothermal fixed bed reactor for producing syngas using partial oxidation process of methane. To obtain more knowledge on reverse flow reactor for partial oxidation of methane to syngas, the properties of materials and the more complex model such as heterogeneous model should be investigated. It will be more useful for design and control of this kind of reactor.